The influence of understanding tri n and procrastination on students’ intention to commit academic fraud - Wardani, Dewi Kusuma; Atih, Mirka Atul Mafa (Proceeding International Conference on Accounting and Finance, 2024)
The aim of this study is to investigate how the understanding of Tri N-laere and procrastination affects students’ choice to commit academic fraud. All students currently enrolled in accounting at Sarjanawiyata Tamansiswa University’s Faculty of Economics in the cohorts of 2020, 2021 and 2022 are included in this study. When the snowball technique was used, a sample of 142 respondents was selected using Google Forms. The data testing results show that understanding Tri N has a negative impact on students’ intention to commit academic fraud. On the other hand, procrastination has no impact on students’ intention to commit academic fraud.